(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
It is shown that in Ukraine the network of territorial communities is too shredded, and therefore rather costly, in particular, in terms of spending on the management and maintenance of social infrastructure. Accordingly, the task of building an effective system of territorial organization of power and the formation of capable (in the economic and social sense) of territorial communities is relevant. It is noted that the official methodology for the formation (association) of territorial communities should be adjusted in such a way that united communities do not cover the whole area, otherwise it will greatly complicate the provision of public services, in particular emergency ones. To optimize the networks of schools, hospitals and other institutions, it is proposed to introduce criteria for the allocation in the combined territorial communities of the capable central and pastoral districts. A scientific approach has been applied to correct «distortions» in the formation of capable territorial communities, which should ensure the creation of optimal communities. The difficulties with the formation of united territorial communities, which are primarily related to the financial and economic weakness of village and settlement councils, in particular those where industrial enterprises were liquidated under market conditions, were noted. The forecast of the network of territorial communities of Chudnovsky district of Zhytomyr region is presented, taking into account their socioeconomic capacity. The reasons for the formation of «white spots» on the map of the combined territorial communities of the Chudnovsky district were revealed. Formation of capable territorial communities is defined as a strategically important direction of socio-economic development of rural territories. For specific territorial communities, prospective directions of strengthening of their economic base and preservation and improvement of networks of social infrastructure objects are indicated. The conclusion is made of the need for active participation of state bodies in the economic revival of territorial communities.